Analysis of the Location of Rescue Ambulance Dispatch Bases: A Case Study in Rio de Janeiro, Brazil. Issue 4 (8th October 2018) - Ferrari, Thayse; Camara, Marcus Vinicius Oliveira; Nassi, Carlos David; Ribeiro, Glaydston Mattos; Costa Junior, Roberto Robadey; Ribeiro Júnior, Célio; Bilate, Andrea
Abstract : Emergency Medical Services are considered critical elements of modern health services, to assure the appropriate level of service to the population. We applied the facility location theory to indicate strategic points to establish ambulance dispatch centers to attend emergency calls. Therefore, the main objective of this paper is to promote an analysis of the locations of rescue ambulance bases in the city of Rio de Janeiro, focusing on reducing the response time of calls. We propose a mathematical model which aims at maximizing the number of people served by the ambulance dispatch bases and the different types of calls answered (general or calls related to traffic accidents), and minimizing the number of ambulance dispatch centers and the distances from demand points to centers. We used a real dataset from 2014 (approximately 105, 000 emergency calls) to perform our evaluations. We concluded that two planning areas exist with potential to improve the service, and with the inclusion of 10 new dispatch bases in the areas with low coverage and only five new vehicles in the system, the number of attended people would increase by 6.4% in relation to the current situation (approximately 409, 000 inhabitants served).